The role of self-efficacy beliefs in dealing with misinformation among adolescents - Paciello, Marinella; Corbelli, Giuseppe; D’Errico, Francesca (Frontiers in Psychology, 2023)
The present study aims to understand the processes involved in misinformation among adolescents by examining the role of self-efficacy beliefs in dealing with misleading news. Specifically, we argue that the perceived capability to analyze and reflect critically on the reliability of online information sources should be stayed with the perceived self-regulatory capability to resist online social pressures to share unverifiable news. Moreover, we posited that specific online self-efficacies beliefs can be promoted by the capabilities related to regulating emotions and reflecting on new problems. In a sample of 273, we tested a path analysis model. The results attest that self-efficacy beliefs in dealing with online misinformation refer to specific capabilities: an active one, related to checking the sources of the news in order to validate their content, and an inhibitory one, related to the capability to refrain from sharing the news that seems unreliable. Moreover, self-efficacy beliefs in self-control during online interaction spreading misleading news are supported by cognitive reflective capability and self-efficacy in regulating negative emotion. The relationship between active self-efficacy related to fact-checking and sharing misleading news is not significant. The role of regulation in sharing misinformation during activated online dynamics is discussed.